Canary seed flour as a promising new ingredient for gluten-free cookies - Gozzi, Marta Sofía; Rosito, Pablo; Cisternas, M. Estefania; Fiorito, Romina; Játiva Gutiérrez, M. Paola; Ormando, Paula (Ediciones INTA, 2025)
Food science and gastronomy collaborate to provide healthy, customized options, including gluten- free food for people with celiac disease. Hairless canaryseed (Phalaris canariensis L.) is considered a gluten-free cereal with a good nutritional profile. The aim of this work was to characterize hairless canaryseed flour (CSF) as a new ingredient and the effect of its incorporation (0% Control, 15% [R15] and 35% [R35] to weight flour) in gluten-free cookies. The chemical composition, carotenoids, minerals, and color were determined. Also, the physical, mechanical and sensory parameters of the cookies were evaluated. The results showed an increase in protein (5.98-9.27%), ash (1.42-2.5%) and mineral content (iron 1.62-2.55 mg%, magnesium 15.63-46.13 mg%, potassium 70.75-125.60 mg%), and a decrease in lightness (74.30-60.93). Fortification increased the thickness of the cookies, while it also decreased the spread ratio and hardness. Sensorially, the enriched cookies had good acceptability, with color being the only parameter in which significant differences were observed. The results showed that CSF can be used to enhance the nutritional, physical, and sensory characteristics of gluten-free cookies.